De escrituras autobiográficas e hibridismos en los géneros literarios - Fallas Arias, Teresa (2012)
The study of the practices of female autobiographical writings is the excuse to explore the perspectives that scholars have maintained, through time, with respect to literary genres. In their approach it has become clear is the hybridity that characterizes them, from its origin, and the folding-unfolding game staged as a result of controversial rhythm makers, advocates, and offenders of such generic categories.